STRATEGI MENINGKATKAN LITERASI DIGITAL DI MA’HAD ALY (Studi pada Mahad Aly Miftahul Huda Manonjaya Tasikmalaya) - Saridudin (Program Studi Pendidikan Agama Islam, 2024)
The research aims to analyze and understand the strategies and efforts made by Ma'had Aly Miftahul Huda Manonjaya Tasikmalaya in an effort to develop digital literacy among the academic community, especially lecturers and students. This research uses a qualitative phenomenology type approach, where the researcher seeks to understand the phenomena that occur and develop. Data collection techniques are carried out through observation, interviews and documentation. Data analysis was carried out through the stages of data presentation, data reduction and drawing conclusions. The results of the research show that digital literacy carried out by Ma'had Aly Miftahul Huda Manonjaya aims to improve the quality of Ma'had Aly graduates so that they become graduates who are competent in the field of tafaqquh fiddin, especially in the fields of Islamic faith and philosophy. The strategy implemented by Ma'had Aly Miftahul Huda Manonjaya's aim to increase digital literacy is to train students to be able to create digital content that can be broadcast on TV and Live Streaming on Facebook. Apart from that, Mahad Aly Miftahul Huda is optimizing the television channel managed by the Islamic boarding school, the television is called MH TV (Miftahul Huda TV), which is filled with various programs, one of which is Ngaji Online.